International human rights protection : balanced, critical, realistic - Bossuyt, Marc J.; Boven, Th. C. van; Mahoney, Paul (Cambridge, United Kingdom ; Cambridge, United Kingdom ; Portland [Oregon] : Intersentia Ltd, 2016)
"[This book] is based on the author's personal research and personal involvement with a wide range of subjects, such as: the basic concepts of civil and social rights; discrimination and affirmative action; issues of procedure and jurisdiction; the death penalty; and issues such as the protection of refugees, minorities and victims of armed conflicts. At the universal level, the book introduces the reader to the labyrinth of United Nations Charter-based and treaty-based procedures. As well as an overview of the Inter-American and African systems, it deals at the regional level-particularly with the case law of the European Court of Human Rights in Strasbourg, and also looks at the national level at the case law of the US Supreme Court and the South African Constitutional Court. This book adopts a particularly critical approach to the so-called 'dynamic' interpretation of the European Convention on Human Rights by the Court of Strasbourg. It is the author's feeling that judges, in particular those belonging to courts specialising in human rights, have a tendency to systematically support interpretations benefiting the applicants, while overlooking too easily the far-reaching implications of judgments for society as a whole. The author, instead, puts forward a more balanced and more realistic approach which takes into account the difficulties democratic governments face in coping with the challenges of our present time and with the pressing needs of the realities of today's world."--
The concept of human rights -- Social rights : a specific category of human rights? -- The prohibition of discrimination -- The concept of affirmative action -- The UN charter-based human rights bodies -- The UN human rights treaty bodies -- Regional systems of protection of human rights -- Procedural issues at the Durban Conference Against Racism -- The internal applicability of human rights treaty provisions -- The death penalty and irreducible life sentences -- Limits to the jurisdiction of the Court of Strasbourg? -- The Court of Strasbourg and positive obligations -- The protection of refugees in international law -- The protection of minorities in international law -- The protection of victims of armed conflicts.
Includes bibliographical references (pages 207-230).
Keywords: Human rights; International human rights courts -- Europe; Human rights; International human rights courts; Europe